The Negro in the French West Indies - McCloy, Shelby T. (Shelby Thomas), 1898-1973 (Book collections on Project MUSE., 1966)
In the research for his book on the opportunities of the black population in Metropolitan France, Shelby T. McCloy found the treatment accorded to people of color in the French colonies so significantly different as to warrant a separate book. This historical study examines the black experience in the French West Indies -- the islands of Martinique, Guadeloupe, and Santo Domingo -- from the days of slavery and the brutal Code Noir through struggle and revolution to freedom. McCloy provides a detailed account of the black popluation's increasingly important place in the islands from early in t.